Cynaropicrin targets the trypanothione redox system in Trypanosoma brucei - Zimmermann, Stefanie; Leroux, Alejandro E.; Krauth-Siegel, Renate (Bioorganic & medicinal chemistry, 2013)
In mice cynaropicrin (CYN) potently inhibits the proliferation of Trypanosoma brucei—the causative agent of Human African Trypanosomiasis—by a so far unknown mechanism. We hypothesized that CYNs α,β-unsaturated methylene moieties act as Michael acceptors for glutathione (GSH) and trypanothione (T(SH)2), the main low molecular mass thiols essential for unique redox metabolism of these parasites. The analysis of this putative mechanism and the effects of CYN on enzymes of the T(SH)2 redox metabolism including trypanothione reductase, trypanothione synthetase, glutathione-S-transferase, and ornithine decarboxylase are shown. A two step extraction protocol with subsequent UPLC-MS/MS analysis was established to quantify intra-cellular CYN, T(SH)2, GSH, as well as GS-CYN and T(S-CYN)2 adducts in intact T. b. rhodesiense cells. Within minutes of exposure to CYN, the cellular GSH and T(SH)2 pools were entirely depleted, and the parasites entered an apoptotic stage and died. CYN also showed inhibition of the ornithine decarboxylase similar to the positive control eflornithine. Significant interactions with the other enzymes involved in the T(SH)2 redox metabolism were not observed. Alongside many other biological activities sesquiterpene lactones including CYN have shown antitrypanosomal effects, which have been postulated to be linked to formation of Michael adducts with cellular nucleophiles. Here the interaction of CYN with biological thiols in a cellular system in general, and with trypanosomal T(SH)2 redox metabolism in particular, thus offering a molecular explanation for the antitrypanosomal activity is demonstrated. At the same time, the study provides a novel extraction and analysis protocol for components of the trypanosomal thiol metabolism.